Pencil & Eraser. 3, new friends rule! - Alvarado, Jenny (Alvarado, Jenny. Pencil & Eraser (Series), 2026)
"When Pencil befriends an eager Ruler, Eraser struggles to adjust to the new friendship dynamic on a mission to rescue a missing crayon"-- Provided by publisher.